1988
DOI: 10.2466/pr0.1988.62.1.271
|View full text |Cite
|
Sign up to set email alerts
|

Contributions to the History of Psychology: XLVI. The Pioneer Work of Alfred Binet on Children as Eyewitnesses

Abstract: The pioneer work of Alfred Binet (1857–1911) on eyewitness testimony (1900) often is cited today in support for a traditional view of the extreme suggestibility of children. Binet, on the other hand, interpreted his findings as showing that suggestibility is not a static trait among children but rather is a function of cognitive and social factors associated with attempts to influence during interrogation. Ironically, those conclusions made nearly 90 years ago are mirrored in modern conceptualizations of the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…A similar appraisal led Cunningham (1988) to devote an article to Binet's research on how suggestibility influences children's memory. Binet (1900) presented 7to 14-year-olds a poster with a number of objects and a depiction of a scene on it.…”
Section: Robert S Sleglermentioning
confidence: 98%
See 2 more Smart Citations
“…A similar appraisal led Cunningham (1988) to devote an article to Binet's research on how suggestibility influences children's memory. Binet (1900) presented 7to 14-year-olds a poster with a number of objects and a depiction of a scene on it.…”
Section: Robert S Sleglermentioning
confidence: 98%
“…Although THE OTHER ALFRED BINET I89 the particular answer advanced by the leader varied among the groups, few children challenged whatever answer the leader advanced, even when it was plainly wrong. Binet's comment on the implications of this finding: "Woe betide him who is alone" (Cunningham, 1988).…”
Section: Robert S Sleglermentioning
confidence: 99%
See 1 more Smart Citation
“…When he found that the memory of these participants could be influenced by simple suggestions, Binet did not conduct his experiments in the psychological laboratory at the Sorbonne but in classrooms. He had child participants engaged in a series of experiments that helped establish a scientific foundation for the psychology of testimony (Loftus, 1979;Nicolas & Levine, 2012;Nicolas, Collins, Gounden, & Roediger, 2011b;Stern, 1939) and culminated in insightful observation on the phenomenon of social influence (Cunningham, 1988;Roediger, Meade, & Bergman, 2001). Ceci and Bruck's (1995) book on children's testimony had a nice discussion of Binet and his contributions at the time (see also Nicolas, Gounden, & Sanitioso, 2011a).…”
Section: Dormancy Of the Laboratory (1897-1911) But Innovative Studie...mentioning
confidence: 99%
“…For several months, he was able to study children and adolescents, and found that these participants' memories could be influenced by simple suggestions. Beginning with basic laboratory tasks (Binet & Henri, 1894b; for an English translation see Nicolas, Collins, Gounden, & Roediger, 2011a), Binet had child participants engage in a series of experiments that helped to establish a scientific foundation for a psychology of testimony (Loftus, 1979;Nicolas, Collins, Gounden, & Roediger, 2011b;Stern, 1939) and culminated in insightful observations on the phenomenon of social influence (Cunningham, 1988;Roediger, Meade, & Bergman, 2001). Ceci and Bruck's book (1995) on child testimony included a valuable discussion of Binet and his contributions.…”
Section: Suggestibility and Testimonymentioning
confidence: 99%